“LIFE, LIBERTY, AND THE PURSUIT OF HAPPINESS”: MARTIN LUTHER KING’S PROVERBIAL STRUGGLE FOR EQUALITY - Mieder, Wolfgang (Proverbium - Yearbook, 2011)
In barely forty years of life Martin Luther King (1929-1968) distinguished himself as one of the greatest social reformers of modern times. A vast array of biographies and studies have celebrated him as a civil rights leader, a defender of nonviolence in the struggle of desegregation, a champion of the poor, an anti-war proponent, and a broadminded visionary of an interrelated world of free people. His large amount of verbal and written communications in the form of sermons, speeches, interviews, letters, essays, and several books are replete with Bible proverbs as “Love your enemies”, “He who lives by the sword shall perish by the sword”, and “Man does not live by bread alone” as well as folk proverbs as “Time and tide wait for no man”, “Last hired, first fired”, “No gain without pain”, and “Making a way out of no way.” He also delights in citing quotations that have long become proverbs, to wit “No man is an island”, “All men are created equal”, and “No lie can live forever.” King recycles these bits of traditional wisdom in various contexts, varying his proverbial messages as he addresses the multifaceted issues of civil rights. His rhetorical prowess is thus informed to a considerable degree by his effective use of his repertoire of proverbs which he frequently uses as leitmotifs or amasses into set pieces of fixed phrases to be employed repeatedly.